IDENTIFIKASI SENYAWA ANTIRADIKAL BEBAS PADA RUMPUT LAUT Sargassum ringgoldianum - Dira Swantara, I M.; Bawa Putra, A. A.; Surya Udayana, I P. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012)
The identification of antiradical compounds from Sargassum ringgoldianum seaweed has been conducted. Its metabolite extraction was carried out by maceration using ethanol and acetit acid mixture with ratio 9:1. It produced 7,02 gram crude extract from 230 grams of sample pollen. This crude extract has free-radical reduction activity of 66,50% at the fifth minute and 78,77% at the sixtieth minute. Separation and purification were carried out by partition, thin layer chromatography, and column chromatography. Partition was accomplished using petroleum ether, chloroform, ethyl acetate, and also water. Petroleum ether ectract had the highest free-radical reduction percentage, of 76,21%, which was obtained on the fifth minute, and 91,16% on the sixtieth minute. The petroleum ether extract was further separated with column chromatography, using stationary phase of silica gel 60 and mobile phase of a mixture of petroleum ether : acetone (7:3) and produced five fractions (FA, FB, FC, FD, dan FE). The most active fraction with antiradical activity was fraction B with percentage of free-radical reduction of 62,77% on the fifth minute and 92,19% on the sixtieth minute. This activity equals 93,06% of the antiradical activity of vitamin E. Fraction B was identified to consist of six compounds : ethyl myristate; dibutyl phthalate; ethyl palmitate; methyl isostearate; dioctyl phthalate; and 3?-bromo cholest-5-ene.
Keywords: identification, antiradical, Sargassum ringgoldianum seaweed, gas chromatography-mass spectrometer